(untitled) (Research, Society and Development, 2023)
The objective of the present study was to carry out a survey of published productions about suicide in adolescence. This is a narrative review of the literature. The databases used were: SCIELO; LILACS Literature and Virtual Health Library. Inclusion criteria were scientific articles published from 2014 to 2023, in Portuguese, available in full, online and free, that present empirical studies and that portray the proposed theme, in which 8 articles were selected after thorough reading. Suicidal ideation among adolescents may be related to common changes in this period of life, as well as various environmental, sociocultural and existence factors. Among the main risk factors, depression stands out as having a fundamental role in the development of death thoughts and behavior. Knowing the main risk factors for suicide and the different forms of manifestation of the signs can be an important step in planning prevention programs. Nurses play a fundamental role in the recovery of a victim of a suicide attempt. Adolescents can find a support point in the nursing team, acceptance at the time of suffering and thus talk about what ails them. Analyzes of more recent studies broaden the understanding of the factors that predispose to suicidal behavior, indicating that, in order to act preventively in the face of suicidal behavior, it is necessary to be aware and alert to the various risk and protective factors.